Northern Shrimp (Pandalus borealis) on Flemish Cap in July 2002 - Río-Iglesias, José Luis del; Casas-Sánchez, José Miguel; Patrocinio, Teodoro (2002)
A stratified random bottom trawl survey on Flemish Cap was carried out on July 2002. Results on shrimp from the survey are presented and compared to those from previous surveys of the same series. The total biomass index obtained this year, 18 109 tons, is the highest in the series. The female biomass remains at a high level, and it is dominated by age 5 shrimp. Mean lengths at age, abundance and biomass by age are presented.